DIAGNOSIS DAN TATALAKSANA KOMPREHENSIF OSTEOARTRITIS - Winangun Winangun (JURNAL KEDOKTERAN, 2019)
Rheumatic conditions are composed of arthritis and its allied connective tissue diseases. There arecurrently more than 100 discrete forms of arthritis recognized, the most common being osteoarthritis (OA). Osteoarthritis refers to a clinical syndrome of joint pain accompanied by varying degrees of functional limitation and reduced quality of life. It is the most common form of arthritis, and one of the leading causes of pain and disability world wide. The most commonly affected peripheral joints are the knees, hips and small hand joints. Arthritis and related conditions are the leading cause of disability in many countries worldwide. Arthritis and rheumatism, along with back problems, account for approximately one in every three cases of disability.Pain, reduced function and effects on a person's ability to carry out their day-to-day activities. Epidemiology Arthritis is often categorized by its distribution (monoarticular vs. polyarticular); its association with detectable autoantibody(seropositive vs. seronegative); or the degree of underlying inflammation involved (inflammatoryvs. noninflammatory. (The US Centers forDisease Control and Prevention (CDC) estimatesthat nearly 20% of American adults suffer from physician-diagnosed arthritis. Similar prevalen cerates of arthritis have been reported from other developed countries. With an aging population, the burden posed by arthritis and its allied health conditions is expected to grow, with more than 67million adults expected to have arthritis in the next 20 years. Pathofisiology Osteoarthritis is characterised pathologically by localised loss of cartilage, remodelling of adjacent bone and associated inflammation. A variety of traumas may trigger the need for a joint to repair itself. Osteoarthritis includes a slow but efficient repair process that often compensates for the initial trauma, resulting in a structurally altered but symptom-free joint. There is often a poor link between changes visible on an X-ray and symptoms of osteoarthritis: minimal changes can be associated with a lot of pain, or modest structural changes to joints can occur with minimal accompanying symptoms.Pain in itself is also a complex biopsychosocial issue, related in part to a person's expectations and self-efficacy. Holistic approach to osteoarthritis assessment and management Offer advice on the following core treatments to all people with clinical osteoarthritis. Access to appropriate information activity and exercise Interventions to achieve weight loss if the person is overweight.There are a number of management and treatment options (both pharmacological and non-pharmacological), which this guideline addresses and which represent effective interventions for controlling symptoms and improving function. Advise people with osteoarthritis to exercise as a core treatment irrespective of age, comorbidity, pain severity or disability. Exercise should include: Local muscle strengthening and general aerobic fitness. It has not been specified whether exercise should be provided will depend upon the person's individual needs,circumstances ,motivation, and the availability of local facilities Recent improvements in understanding of immunology and disease pathogenesis have led to seminal advances in the management of the rheumatic diseases. In the last decade alone, there have been at least seven biologic, seasemodifying, antirheumatic drugs (DMARDs)approved for the treatment of RA, with many of these agents also approved for the treatment of juvenile idiopathic arthritis (JIA), seronegative spondyloarthropathy, Guideline update was originally intended to include recommendations based on a review of new evidence about the use of paracetamol, etoricoxib and fixed-dose combinations of NSAIDs (non-steroidal anti-inflammatory drugs) plus gastroprotective agents in the management of osteoarthritis. Refer for consideration of joint surgery before there is prolonged and established functional limitation and severe pain . Oral analgesics Healthcare professionals should consider offering paracetamol for pain relief in addition to core treatments regular dosing may be required. Paracetamol and/or topical non-steroidal anti-inflammatory drugs (NSAIDs) should be considered ahead of oral NSAIDs, cyclo-oxygenase 2 (COX-2) inhibitors or opioids.. Although NSAIDs and COX-2 inhibitors may be regarded as a single drug class of 'NSAIDs', these recommendations use the two terms for clarity and because of the differences in side-effect profile. Where paracetamol or topical NSAIDs are ineffective for pain relief for people with osteoarthritis, then substitution with an oral NSAID/COX-2 inhibitor should be considered. Use oral NSAIDs/COX-2 inhibitors at the lowest effective dose for the shortest possible period of time. When offering treatment with an oral NSAID/COX-2 inhibitor, the first choice should be either a standard NSAID or a COX-2 inhibitor (other than etoricoxib 60 mg). In either case, co-prescribe with a proton pump inhibitor (PPI), choosing the one with the lowest acquisition cost. All oral NSAIDs/COX-2 inhibitors have analgesic effects of a similar magnitude but vary in their potential gastrointestinal, liver and cardio-renal toxicity; therefore, when choosing the agent and dose, take into account individual patient risk factors. Topical treatments Consider topical NSAIDs for pain relief in addition to core treatments for people with knee or hand osteoarthritis. Consider topical NSAIDs and/or paracetamol ahead of oral NSAIDs, COX-2 inhibitors or opioids. Topical capsaicin should be considered as an adjunct to core treatments for knee or hand osteoarthritis. Do not offer rubefacients for treating osteoarthritis Intra-articular injections Intra-articular corticosteroid injections should be considered as an adjunct to core treatments for the relief of moderate to severe pain in people with osteoarthritis. Do not offer intra-articular hyaluronan injections for the management of osteoarthritis Aids and devices Offer advice on appropriate footwear (including shock-absorbing properties) as part of core treatments people with lower limb osteoarthritis People with osteoarthritis who have biomechanical joint pain or instability should be considered for assessment for bracing/joint supports/insoles as an adjunct to their core treatments. Assistive devices (for example, walking sticks and tap turners) should be considered as adjuncts to core treatments for people with osteoarthritis who have specific problems with activities of daily living. Offer regular reviews to all people with symptomatic osteoarthritis. Reviews should include: monitoring the person's symptoms and the ongoing impact of the condition on their everyday activities and quality of life ,monitoring the long-term course of the condition ,discussing the person's, their personal preferences and their ability to access services,reviewing the effectiveness and tolerability of all treatments and support for self-management.